PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT BERBANTUAN MEDIA KARTU POSINEGA UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT SISWA KELAS VII SMP NEGERI 15 PALU - Rafiqa N.S., Shara (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain description about applying Cooperative Learning of NHT with the assist of Posinega card able to improve student concept understanding on addition and subtraction of integer. This research was a classroom action research which refers to the Kemmisâ and Mc. Taggartâs design, that is plan, action and observation, and reflection. This research consist of two cycles, and each of the cycles was held in two meeting. The results of this research indicating that through applying of Cooperative Learning of NHT student concept understanding can increased, with the steps of Cooperative Learning of NHT (1) convey the learning purpose and motivating, (2) Presenting information, (3) numbering, (4) questioning, (5) heads together, (6) answering, and (7) giving appreciation. At the 1th phase, researcher convey the learning purpose and benefit to motivate the students; at the 2nd phase, researcherÂ presented addition and subtraction of integer through the demonstration of posinega card usage; at the 3rd phase, researcher divided the students into some groups, and gave number to each member of group; at the 4th phase, researcher gave task in worksheet to the students; at the 5th phase, the students were asked to think together in doing their worksheet and researcher guided them to do that; at the 6th phase,Â researcher mentioned one number and the students who have the number presented their worksheet in front of the class; and at the 7th phase, researcher gave appreciation to each group.